PERTANGGUNGJAWABAN PIDANA DISTRIBUSI OBAT ABORTUS ILEGAL DI PLATFORM E-COMMERCE INDONESIA - Nadiariani, Arista; Tridewo, Naura Fairusyifa; Hosnah, Asmak Ul (Fakultas Hukum Universitas Muhammadiyah Cirebon, 2025)
The distribution of illegal abortion drugs through e-commerce platforms has become a real threat to public health and a violation of the law in Indonesia. This study aims to evaluate the criminal liability of perpetrators of illegal abortion drug distribution within the context of the Criminal Code (KUHP) and the Health Law, focusing on the latest regulatory framework, court decisions, and the role of e-commerce platforms as intermediaries. The methods used are normative juridical research and analysis of court decisions and supervisory data from the Food and Drug Authority (BPOM). The results indicate that in addition to criminal sanctions against sellers and users of illegal abortion drugs under the Health Law and the Criminal Code, there are gaps in law enforcement related to e-commerce platforms, particularly the responsibility of marketplaces. It is recommended that regulations and oversight be strengthened, including seller verification mechanisms, product transparency, and standardized penalties to provide a deterrent effect.